2007
DOI: 10.1097/01.aog.0000250469.23047.73
|View full text |Cite
|
Sign up to set email alerts
|

Risks of Adverse Outcomes in the Next Birth After a First Cesarean Delivery

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
103
2
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(131 citation statements)
references
References 18 publications
14
103
2
9
Order By: Relevance
“…However, if spontaneous labour did not develop by 3-4 days prior to her UL-OTD, then she was offered rb_IOL so that she could deliver 1-3 days before her UL-OTD. In addition, if a woman was scheduled for a rb_IOL but her cervix was not favorable (i.e., modified cervical Bishop's score < 6 21 ), then cervical ripening was promoted using Prostaglandin E2 pledget (Cervidil) and/or PGE2 gel (Propess). The protocol for cervical ripening and IOL used at Mandic Hospital is included as Appendix B.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if spontaneous labour did not develop by 3-4 days prior to her UL-OTD, then she was offered rb_IOL so that she could deliver 1-3 days before her UL-OTD. In addition, if a woman was scheduled for a rb_IOL but her cervix was not favorable (i.e., modified cervical Bishop's score < 6 21 ), then cervical ripening was promoted using Prostaglandin E2 pledget (Cervidil) and/or PGE2 gel (Propess). The protocol for cervical ripening and IOL used at Mandic Hospital is included as Appendix B.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, CD is associated with longer hospital stays for both mother and baby [18,19], increased frequency of serious complications during future pregnancies [18], and higher costs [20]. Despite suggestions that elective CD might improve maternal perineal health [21,22], its long-term benefits are unproven [16,23], and its long-term risks have probably been minimized [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Our observations are comparable with a study 14 which found that compared with mothers who had primary vaginal births, mothers who had primary cesarean section and underwent labor in the second birth were at increased risk of uterine rupture, peripartum hysterectomy, postpartum hemorrhage (PPH) following vaginal delivery, manual removal of placenta, infection and intensive care unit (ICU) admission. Another study 15 To conclude the discussion about obstetric outcomes we observed increased risk of maternal complications and repeat cesarean section following previous cesarean section. About perinatal morbidity and mortality we observed in our study no significant difference in both the groups regarding perinatal outcome.…”
Section: Discussionmentioning
confidence: 93%
“…This is because the anatomy in women with one or more CS can be very different, and for this reason, some passages in performing this operation have an increased risk of complication (malpresentation, placenta previa, antepartum hemorrhage, placenta accreta, prolonged labor, uterine rupture, preterm birth, low birth weight, and stillbirth) [28]. However, some authors define that some risks may be due to confounding factors related to the indication for the first cesarean section, rather than due to the procedure itself.…”
Section: Commentmentioning
confidence: 99%